Bath Salts in the Emergency Department. Issue 2 (March 2015) - Vazirian, Mohsen; Jerry, Jason M.; James, Jeffrey; Dale, Roman M.
<x xml:space="preserve">Abstract</x> Objectives: Several novel synthetic amphetamines have been marketed worldwide as "bath salts." The use of bath salts is associated with severe medical consequences resulting in a US federal ban over the last 3 years on the more common substances found in this group. Bath salts intoxication has a relatively nonspecific presentation, and urine toxicology confirmation in emergency departments (EDs) is impractical because the turnaround time is several days. Emergency clinicians must therefore rely heavily on patients' self-reports to verify the diagnosis. We performed an online survey of emergency clinicians to determine their degree of exposure to bath salts-intoxicated patients, the clinically relevant features of such patients, and the typical emergency management. Methods: We invited 124 physicians and physician assistants in 7 Cleveland Clinic EDs to participate in an online survey. Results: From a total of 43 of the 124 respondents, 77% did not specifically ask patients about bath salts use. Sixty percent had encountered a bath salts-intoxicated individual. Most respondents reported that the majority of patients were male, were between 19 and 29 years old, and used other drugs in addition to bath salts. Agitation, aggression/violence, and hallucinations were reported to be the most common presentations, and intravenous/intramuscular tranquilization was reported as the most often used management. Most patients were discharged home from the ED. Conclusions: Despite the lack of toxicology screening in EDs, about two thirds of the surveyed emergency clinicians encountered bath salts-intoxicated individuals. Our study demonstrates the need for increased screening of bath salts intoxication in EDs, especially in agitated patients.